Human leukocyte antigens class II genes are associated with cancer development in the autoimmune rheumatic diseases - Miranda-Duarte, Antonio; Kraus-Weisman, Arnoldo; Granados, Julio (My University, 2011)
Objective. To t vb determine the association between HLA class II alleles and the probability of developing cancer in patients with autoimmune rheumatic diseases. Material and methods. A a r . matched case control study was conducted in which patients with autoimmune rheumatic disease who later developed malignancy (solid or lymphoproliferative) were compared with matched controls suffering from the same auto-immune rheumatic disease and with similar disease duration. The rheumatic diseases included rheumatoid arthritis, systemic lupus erythematosus, primary Sjögren syndrome, dermatomyositis-polymyositis, and systemic sclerosis. HLA-DR typing was performed by sequence-specific primers after DNA amplification by PCR (PCR-SSP). Statistical analysis was conducted by conditional logistic regression.

Objetivo: Determinar la asociación entre los alelos HLA de clase II y la probabilidad de desarrollar cáncer en pacientes con enfermedades reumáticas autoinmunes. Material y a métodos. Estudio de casos y controles pareado en el que los pacientes con enfermedad reumática autoinmune, que desarrollaron posteriormente un tumor maligno (sólido o linfoproliferativo), fueron comparados con controles pareados por la misma enfermedad reumática autoinmune, sin cáncer y con una duración similar de la enfermedad. Las enfermedades reumáticas incluyeron artritis reumatoide, lupus eritematoso sistémico, síndrome de Sjögren primario, dermatomiositispolimiositis y esclerosis sistémica. La tipificación de HLA-DR fue realizada por iniciadores secuencia específico después de la amplificación de ADN por PCR (PCR-SSP). El análisis estadístico se realizó mediante regresión logística no condicional.